Associação entre nível de atividade física, indicadores de saúde e qualidade de vida de idosos da Universidade da Maturidade - Baptista, Aline Monique Galdiano Silva (Universidade Federal do Tocantins, 2018)
Population aging is a worldwide reality that has been occurring in an accelerated way in recent decades, and is accompanied by physical inactivity. As chronological age increases, people become less active. On the other hand, an active lifestyle is associated with a better quality of life in the elderly. The objective of this research was to verify the association between physical activity level, health indicators and quality of life variables in the UMA / UFT elderly, in Palmas-TO. Methodology: 59 elderly people of both sexes participated in this study. Socio-demographic information, presence of pathologies through self-report, medications used, nutritional status was evaluated by MAN and anthropometry, palmar grip strength (FPP) by Jamar dynamometer, level of physical activity by IPAQ-short version and evaluation of quality of life by the SF-36. Data were presented through descriptive statistics and Pearson's Correlation Coefficient. The SPSS software, version 19.0, was used to perform all the analyzes, adopting the significance of 95%. RESULTS: The mean age of the elderly was 67.77 ± 7.19 years, and 66.10% of them had an insufficient level of physical activity (59.7%). AF). Statistical significance was found among the elderly classified as insufficiently active and sufficiently active in the FPP (p = 0.019), sex (p = 0.006) and three QL domains: CF (0.048), Pain (0.049) and VIT (0.047). The FPP variable correlated positively and significantly with the CF (p = 0.011) and Pain (p = 0.03) domains of SF-36. Conclusion: The elderly presented satisfactory levels of QoL despite the low level of physical activity, low socioeconomic status and chronic health conditions, demonstrating the multidimensional character of the QoL and the PPF was an important factor in their determinants. Thus, it is suggested that UMA / UFT can contribute positively to better QoL and to a healthier and more active aging.